Minat Siswi Dalam Mengikuti Ekstrakurikuler Futsal Di Sma Negeri 1 Banyuasin 1 - Ahmad R Putra; Rohandi N Satardi; Nursidiq Arizal; Ahmad Hidayat; Kiky Subiyanto (Musamus Journal of Physical Education and Sport (MJPES), 2023)
Physical and sports education is part of the curriculum given to elementary school (SD) to senior high school (SMA) level. With the Penjasorkes in schools, especially high schools, female students can channel their movement abilities. Of the many Physical Education subject matter, there is one material, namely Futsal. Futsal is material that can be obtained from formal and non-formal education. In the process of teaching and learning futsal, the teacher has an important role to increase the interest of his students. To find out the interests of students, must have direct information about the state of interest of these students. What is done is to assess limited external cues such as facial and gesture experiments. Based on this, the purpose of this study was to find out "students' interest in participating in futsal extracurricular activities at SMA Negeri 1 Banyuasin 1". This study used a qualitative approach with a descriptive research type. The population in this study were female students of SMA Negeri 1 Banyuasin 1 who took part in a futsal extracurricular activity. The population size of 20 people in this study is a population study that uses all members of the population who take part in extracurricular futsal. The results of this study that received a Very High score were 2 students (10%), High scores were 9 students 45%), Moderate scores were 4 students (20%), Low scores were 2 students (10%), Very Low scores were 3 female students (15%), as a whole it can be concluded that the interest of female students in participating in futsal extracurricular activities at SMA Negeri 1 Banyuasin 1 is in the high score category of 45%.